Formation and characterization of thin film from the Extraction of tomato for uv photodetector / Myo Myo Thu - Thu, Myo Myo (2017)
New concept of UV photodetector with self-powered and biodegradable features are needed to solve energy and environment. In this work, thin-film tomato was used as an active organic layer in UV photodetector because tomato was also rich in antioxidant. When UV radiation interacts with antioxidant, transfer electrons that involve either releases and traps of electrons may occur. This electron transportation phenomenon can be modulated by applying an external power source. With this concept, tomato has been used for this research. In addition, the effect of drying temperature (60⁰C, 80⁰C, 100⁰C, 120⁰C and 140⁰C) on the structural, chemical, optical, electrical and sensing properties of thin-film tomato was studied. The UV photodetector was made of a sandwich structure of glass substrate/thin-film tomato active layer/ interdigitated aluminium electrode. The optimum drying temperature of the device was 120°C, the highest responsivity percentage difference (70.6%) in positive region is recorded and measured at 0 V with quantum efficiency () of 2.53x10-7 %, R of 0.0519x10-6 A/W, and D* of 0.7645x1021 Jones. Without external power supply (0 V), and yet the photodetector works with the highest responsivity, makes it as an energy saving and self-powered device. Then, it is followed by comparing the properties of thin-film tomato produced from tomato extract with and without oxalic acid. The fabricated using tomato extracted by adding with and without oxalic acid at 120oC, the highest responsivity percentage difference (89.60%) in positive region is recorded in photodetector with thin-film tomato with oxalic acid dried at 120oC and measured at 5 V with quantum efficiency () of 1.0335x10-5 % , R of 2.1178x10-6 A/W, and D* of 1.1649x1021 Jones. Above these results indicate that the thin-film tomato dried at this specific temperature is the best to be used to detect UV-C (254 nm) at 0 V and UV- (302 nm) at 5 V, respectively, and their respective  values are 2.53x10-7 % and 7.7384x10-6 %. The response time for raising and falling for all testing less than 0.3 s observed in this work enables the thin-film tomato being used as a UV photodetector at this specific wavelength. In addition, the performance of the device dependent on the presence of functional groups, the surface roughness and refractive index of thin film tomato. These results had affect the UV absorption that directly influence the radical formation and scavenging activity in tomato, leading to current response of the device. Therefore, the quick response, high responsivity, high detectivity and stability enable the obtained thin-film tomato device to be used as UV photodetector.